2021
DOI: 10.1155/2021/4867942
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hydrogeochemical Characteristics of Tunnel Groundwater Based on Multivariate Statistical Technology

Abstract: Following tunnel excavation, which is influenced by hydraulic fracturing and geological structure, a series of hydrochemical reactions occur in the karst aquifer, which has a significant impact on groundwater hydrology and the earth process. Based on five sets of 38 samples collected in the Tongzi Tunnel in 2020 and 2021, the main geochemical processes and water quality conditions of the karst aquifer system during tunnel construction were revealed by multivariate statistical analysis and graphical methods. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The Gibbs diagram can qualitatively determine the hydrochemical evolution mechanism controlled by atmospheric precipitation, rock filtration, and evaporation concentration [45]. The Gibbs diagram of groundwater in the study area (Figure 6) showed that the groundwater samples were mainly within the TDS concentration range of 10-1000 mg/L, with Na + /(Na + +Ca 2+ ) ratios mainly distributed between 0.1 and 0.7, and Cl − /(Cl − + HCO 3 − ) ratios mainly distributed between 0.0 and 0.5, falling between "rock filtration control" and "evaporation concentration control", indicating that the hydrochemical evolution of groundwater was largely controlled by rock filtration and evaporation concentration, with some groundwater samples falling outside the Gibbs model, possibly due to human activities or cation exchange [46].…”
Section: Primary Stratigraphic Environmentmentioning
confidence: 99%
“…The Gibbs diagram can qualitatively determine the hydrochemical evolution mechanism controlled by atmospheric precipitation, rock filtration, and evaporation concentration [45]. The Gibbs diagram of groundwater in the study area (Figure 6) showed that the groundwater samples were mainly within the TDS concentration range of 10-1000 mg/L, with Na + /(Na + +Ca 2+ ) ratios mainly distributed between 0.1 and 0.7, and Cl − /(Cl − + HCO 3 − ) ratios mainly distributed between 0.0 and 0.5, falling between "rock filtration control" and "evaporation concentration control", indicating that the hydrochemical evolution of groundwater was largely controlled by rock filtration and evaporation concentration, with some groundwater samples falling outside the Gibbs model, possibly due to human activities or cation exchange [46].…”
Section: Primary Stratigraphic Environmentmentioning
confidence: 99%